The Effect of Make a Match Technique Toward Students’ Vocabulary - Sujihan A. Arief; Sri Agriyanti Mestari; Helena Badu (Transbahasa, 2023)
This research intends to find out whether the application of Make A Match technique can enhance students’ vocabulary achievement at SMA Negeri 4 Gorontalo. It was conducted to first grade particularly class X IPA 1 as the sample of this research. The researcher used pre-test post-test design in order to find out the significant difference of students’ vocabulary achievement before and after the application of Make a Match technique. The quantitative method is applied for this research due to this type of research is explaining a phenomenon by collecting numerical data that are analyzed statistically. As the result, after application of Make a Match technique it can be seen that the students’ vocabulary increased. It showed based the result of mean score in pre-test is 16,25 and in post-test increased to 19,3. In addition, the application of this technique made the students actively participate and focus on the vocabulary learning process, interested to follow the learning process due to the learning media and the role that they play during the section. Finally, the students can build communication and corporate with other students.